Characterization of Polysaccharides from Cystocarpic and Tetrasporic Stages of Sub-Antarctic Iridaea Cordata - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B (Elsevier B.V., 2021)
The polysaccharide systems from cystocarpic and tetrasporic phases of the Sub-Antarctic algae Iridaea cordata were studied. Cystocarpic plant polysaccharides are mainly composed by carrageenans of the κ–family. However, agaran structures were also detected in the fraction soluble in 2.00 M KCl, after fractionation with increasing potassium chloride solutions. The presence of β-D-galactose-α-L-galactose 3-sulfate, β-D-galactose-α-L-galactose 6-sufate, β-D-galactose 6-sulfate-α-L-galactose 6-sufate, and of β-D-galactose 4-sulfate-α-L-galactose 2,3-disulfate diads was confirmed by means of methylation and NMR spectroscopy analyses; the latter diad has been scarcely reported. The first extracts from tetrasporic plants rendered a pure λ-carrageenan with considerable yield, which confers this species promising commercial applications. In some cystocarpic and tetrasporic extracts α-glucose was also found and assigned to floridean starch by 1H-13C HSQC NMR spectroscopy. © 2021 Elsevier B.V.